The role of the educat (Journal of the College of Basic Education, 2024)
Despite the awareness and guidance efforts undertaken by educational counselors for students in Iraqi government schools about electronic blackmail and its harms, the researcher noticed, through her experience with some male and female counselors and inspection visits to the progress of practical education in schools, that there are some counselors who do not pay much attention to the harms of electronic blackmail, and this may be due to Some counselors are afraid of school principals and families to talk about it or discuss it effectively, or that some of them need more training and qualification on how to deal with it, which may directly affect the success of the ways educational counselors deal with the harms of electronic blackmail in the required manner. Which leads to a weak focus of educational counselors in building their monthly or annual plans regarding ways to confront or limit the damage of electronic blackmail, which directly affects the decline in students’ academic achievement and the weakness and collapse of the student’s personality, which may sometimes lead students to commit suicide. Therefore, identifying It is clear to the educational counselor’s awareness role in reducing the harms of electronic blackmail in government schools in Basra Governorate, to enable them to help reduce the harms of electronic blackmail in Iraqi society. The study attempted to answer the following questions:1-What is the role of the counselor in reducing electronic blackmail in Basra Governorate schools? 2-Is there a difference in the role of the counselor in reducing electronic blackmail in Basra Governorate schools according to gender, experience, and residence?The importance of the current study is evident in:1-The current study represents a purposeful attempt to help educators and parents follow up on students and encourage them to preserve their personal privacy to avoid falling into blackmail and its social and psychological repercussions and to make them more wise and aware of the consequences of revealing information. As well as controlling their emotions and minds optimally and adopting realistic standards and behavioral goals for personal responsibility. 2-Social media has become the preoccupation of many people, devouring their time Their privacy was published. It got them into unnecessary problems, including electronic blackmail. The study aimed to identify:1-The role of the educational counselor in reducing the harms of electronic blackmail in Basra Governorate.2-Explaining the impact of the study variables (gender, experience, residence) on the role of the educational counselor in reducing the harms of electronic blackmail in government schools in Basra Governorate.The scale was applied to a sample of (116) male and female educational counselors distributed among several schools in Basra Governorate. The researcher decided on the scale (Muatasem 2020), and the number of items was (51). The researcher established validity and reliability for it, and the rating scale was four-pointed (always applies to me = 4. Sometimes applies to me = 3, rarely applies to me = 3, never applies to me = 1. The results of the study were interpreted after using the SPSS statistical package to analyze the data. The researcher reached a set of recommendations, including the necessity of subjecting new educational counselors to training courses while serving in a role. Educational guide to reduce electronic blackmail.